GANGGUAN PSIKOSOMATIK DAN PSIKOFISIOLOGIS (ANOREXIA NERVOSA, ENURESIS, ASHMA) - Sri Yenawati (Psympathic : Jurnal Ilmiah Psikologi, 2010)
Since many centuries ago, psychological factors were considered as an important aspect in treatment of many disease that incurred on human life. Body and mind relation are a very interesting object study for many centuries for many people. Polemics, researches and opinions were aroused time to time—either about its own existence, function and dichotomy between physical and psychological nature of human being. This research emphasizes on dichotomy of physical and psychological nature of human which then resulted in many problems both physical and psychological. In this paper we try to describe some medical disease that occurred in many situations and considered—generally—caused by psychological aspect, including case example, prevention methods, treatment and many other.